2020
DOI: 10.1186/s12916-020-01732-5
|View full text |Cite
|
Sign up to set email alerts
|

Compassionate drug (mis)use during pandemics: lessons for COVID-19 from 2009

Abstract: Background: New emerging infections have no known treatment. Assessing potential drugs for safety and efficacy enables clinicians to make evidence-based treatment decisions and contributes to overall outbreak control. However, it is difficult to launch clinical trials in the unpredictable environment of an outbreak. We conducted a bibliometric systematic review for the 2009 influenza pandemic to determine the speed and quality of evidence generation for treatments. This informs approaches to high-quality evide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Early observational studies of these repurposed medications (alone or in combination with azithromycin) have given divergent results in patients with mild to severe COVID-19 [ 34 ]. Despite the preliminary nature of these studies, the reported results have led to confusion about the usefulness of this treatment and widespread empirical use in some parts of the world [ 37 ]. Large randomised controlled studies have now been performed allowing robust analysis of key outcomes in groups of patients with COVID-19 of diverse severity.…”
Section: Summary Of Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early observational studies of these repurposed medications (alone or in combination with azithromycin) have given divergent results in patients with mild to severe COVID-19 [ 34 ]. Despite the preliminary nature of these studies, the reported results have led to confusion about the usefulness of this treatment and widespread empirical use in some parts of the world [ 37 ]. Large randomised controlled studies have now been performed allowing robust analysis of key outcomes in groups of patients with COVID-19 of diverse severity.…”
Section: Summary Of Recommendationsmentioning
confidence: 99%
“…Randomised clinical trials have been conducted at an unprecedented rate to generate evidence for specific interventions [ 33 ]. During the early stages of the pandemic in particular, empirical use of antiviral and anti-inflammatory drugs such as hydroxychloroquine, lopinavir-ritonavir, remdesivir and monoclonal antibodies was widespread globally in the absence of formal guidelines or randomised trial evidence [ 34 37 ]. It is therefore important to have both recommendations in favour of successful interventions but also evidence to avoid certain therapies if their benefit-risk balance is unfavourable [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is always a temptation for “compassionate use” of biologically plausible agents for individual patients in extremis with no proven treatment option. 47 If however all patients who were treated with steroids/hydroxychloroquine/remdesivir/convalescent plasma had been randomised into trials from the beginning of the pandemic, we would have known whether these agents are beneficial (or indeed harmful) much sooner and more patients could have benefitted from these results. The success of pragmatic trials such as SOLIDARITY/RECOVERY have demonstrated the feasibility of this even in pandemic settings.…”
Section: Discussionmentioning
confidence: 99%
“…A review by the National Academy of Science, Engineering and Medicine from the United States of America (USA), on the international response to the 2014 Ebola outbreak in West Africa, highlighted many apparent errors and lessons to be learned 9 . A key criticism was that small, underpowered clinical trials did not provide answers to help direct clinical care, nor did "compassionate use" trial programmes, since even if treatments were provided to large numbers of individuals, little sense of relative efficacy could be made in the absence of a comparative control arm 10 . Indeed, there was a widespread recognition of the need for randomisation to determine if interventions are effective or not in global health pandemics.…”
Section: Urgent Need For Clinical Trial Efficiency In a Pandemic Settingmentioning
confidence: 99%